Donafenib versus sorafenib in triple therapy for unresectable hepatocellular carcinoma: a propensity score-matched multicenter analysis - Yaohong Wen; Shuyi Zhou; Yuyan Xu; Cheng Zhang; Zhoubin Feng; Yinghui Song; Bai Ding; Chuang Peng; Hongkun Tan; Chunming Wang; Jianan Feng; Jingyuan Pei; et al. (World Journal of Surgical Oncology)
Abstract Background In recent years, triple therapy (molecular targeted agent + PD-1 inhibitor + transarterial therapy) has emerged as a promising strategy for unresectable hepatocellular carcinoma (uHCC). However, the optimal molecular targeted agent choice within triple therapy remains unclear. Donafenib is currently the only targeted drug with superior survival benefits compared with sorafenib monotherapy. This study aimed to compare donafenib-based versus sorafenib-based triple therapy in patients with uHCC, providing preliminary evidence to guide molecular targeted agent selection in this emerging treatment paradigm. Methods This retrospective study enrolled 106 patients with initially uHCC who received triple therapy combining either donafenib or sorafenib with PD-1 inhibitors and transarterial therapies. A 1:2 nearest neighbour propensity score matching was used to minimize selection bias. The primary endpoints were overall survival (OS) and progression-free survival (PFS) based on Kaplan-Meier analysis. The secondary endpoints included objective response rate (ORR), surgical conversion rate and adverse events (AEs). Statistical comparisons used Cox regression for survival data and chi-squared/ t-tests for other metrics, with p < 0.05 indicating significance. Results After matching, 30 patients received sorafenib-based triple therapy (Sor-P-T/H group) and 50 patients received donafenib-based triple therapy (Don-P-T/H group). Although the median OS was not attained, the Don-P-T/H regimen demonstrated a statistically significant survival advantage (HR = 0.317, P = 0.004). Moreover, the Don-P-T/H group demonstrated significantly higher median PFS (9.00 vs. 4.62 months, P = 0.005), ORR (64% vs. 40%, P = 0.037) and surgical conversion rate (26.0% vs. 3.3%, P = 0.01) compared to the Sor-P-T/H group. The two groups showed no notable difference in the overall severity of adverse events but the Don-P-T/H group demonstrated less liver impairment. Conclusion Donafenib may be more advantageous than sorafenib in triple therapy for patients with uHCC.